Carbonic anhydrase 2 is a novel invasion‐associated factor in urinary bladder cancers. Issue 3 (3rd April 2017) - Tachibana, Hirokazu; Gi, Min; Kato, Minoru; Yamano, Shotaro; Fujioka, Masaki; Kakehashi, Anna; Hirayama, Yukiyoshi; Koyama, Yuki; Tamada, Satoshi; Nakatani, Tatsuya; Wanibuchi, Hideki
Abstract : Rat bladder cancer is nearly always papillary non‐invasive urothelial carcinoma (UC). To establish an animal model mimicking invasive UC that arises from papillary non‐invasive UC in the bladder, male human c‐Ha‐ras proto‐oncogene transgenic rats (Hras128) were treated with 0.05% N ‐butyl‐ N ‐(hydroxybutyl)nitrosameine (BBN) in their drinking water and/or 0.1% phenylethyl isothiocyanate (PEITC) in their diet as follows: BBN (8 weeks)→PEITC (8 weeks); PEITC (8 weeks)→BBN (8 weeks); BBN alone (16 weeks); PEITC alone (16 weeks); and no treatment. At the end of week 16, the highest incidence of invasive UC was observed in the BBN→PEITC group. Therefore, we used Hras128 rats treated with BBN followed by PEITC as a model of invasive bladder cancer to identify invasion‐associated proteins. Proteome analysis was performed to compare the protein profiles of invasive and non‐invasive UC in Hras128 rats. We identified 49 proteins that were either overexpressed or underexpressed in invasive UC but not in non‐invasive UC. Immunohistochemical analysis of carbonic anhydrase 2 (CA2), an overexpressed protein, showed that the relative number of CA2‐positive UC was significantly higher for invasive UC compared to non‐invasive UC in rats. Moreover, the incidence of CA2‐positive cancers was also significantly higher for human muscle‐invasive bladder cancer (MIBC) compared to non‐MIBC (NMIBC) and was positively associated with the progression of NMIBC. Our findings indicate that CA2 is an invasion‐associated factor and suggest that it could serve as a potential therapeutic molecular target for bladder cancers. Abstract : Expression of CA2 in the human MIBC.